National Education on the Basis of Serbian Art Music in Primary School - Pavlović, Biljana M.; Cicović Sarajlić, Dragana J. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The paper deals with national education in primary schools on the basis of Serbian art music. On the theoretical level, the task of this paper is to examine the works of the most prominant Serbian composers which should be introduced to elementary school students. The paper presents the results of the research whose aim was to determine to what extent the 8th grade students from the territory of Kosovo and central Serbia know about Serbian art music and how many are familiar with the works of the most prominent Serbian composers. The survey results indicate that students do not know enough about the national art music after finishing primary school. One of the reasons is the insufficient representation of the local authors’ compositions for listening in class. The task of primary school classes is to, in accordance with the national educational policy, strengthen the national spirit among young people and to encourage responsible behavior towards their own national values: language, religion, art, customs, traditions. It was concluded that the selection of content that enables the realization of the tasks of national education must be approached conscientiously and responsibly across all subjects in elementary education. In teaching of music culture, national art music is a subject that, in addition to the traditional, spiritual, and patriotic songs, contributes greatly to the national upbringing. Features of national character today have special educational and social meaning and significance in Kosovo and Metohija, where, due to the specific conditions of life of the Serbian people on this territory, it is necessary to devote more attention to them in the educational work. Introduction of creative works of national composers to elementary school students will contribute to the strengthening of national pride and sense of belonging to their people. The paper cited works of national art music that are unjustly neglected, and which because of their high aesthetic and ethical values ​​should be included in the curricula of music culture. The study applied a descriptive method and the method of theoretical analysis.
Keywords: national education; teaching; elementary school; Serbian national art music